New Approach for Evaluation of a Watershed Ecosystem Service for Avoiding Reservoir Sedimentation and Its Economic Value: A Case Study from Ertan Reservoir in Yalong River, China - Bilige Sude; Wu Nan; Gao Ji-Xi; Zhang Chen; Ge Jing; Ennaanay Driss (Applied and Environmental Soil Science)
A model was established to simulate an ecosystem service of avoiding reservoir sedimentation and its economic value based on the process of sediment delivery in a watershed. The model included fabricating the watershed of the study reservoir. The sediment retention coefficient of different land cover types were used to simulate the spatial patterns of the annual quantity of the sediment that were prevented from entering the reservoir by the vegetation in each cell followed the flow path in watershed. The economic value of the ecosystem service in this model was determined by the marginal cost of reservoir desilting. This study took the Ertan reservoir as an example. The results showed that most eroded soil was intercepted by different types of ecosystems in the process of sediment delivery in a watershed. The region with a higher quantity of sediment retention was around the reservoir. The absolute quantity of average sediment retention in forestland was lower, so the sediment retention ability of forestland failed to be brought into fullest play in watershed.